Literasi Media Sosial Sebagai Antisipasi Hoaks Bagi Organisasi Kemasyarakatan Muslimat NU di Kabupaten Demak - Ulya, Himmatul; Restu Ayu Mumpuni; Nugraheni Arumsari; Siti Muslikhatul Ummah (Jurnal Dharma Indonesia, 2025)
The internet use in Indonesia, particularly among women, has shown significant growth, with a penetration rate reaching 49.1% in 2024. However, this increase has not been matched by a corresponding rise in digital literacy, especially in discerning accurate information, which remains low among housewives. This is evident from various cases of hoax dissemination where women were the primary perpetrators. To address this issue, this community service initiative focuses on the Muslimat NU group in Sayung District, most of whose members are women over 45 years old and active on social media and messaging apps like WhatsApp and Facebook. This program aims to empower and improve the community's well-being by enhancing digital literacy through social media literacy, particularly in knowledge and competency for older women using social media. This group was selected because its characteristics reflect those of "digital immigrants," who are vulnerable to spreading hoaxes due to limited understanding of information and communication technology (ICT) and reside in an area experiencing a digital divide. The activities were conducted using a Participatory Learning and Action (PLA) approach, relying on lectures, discussions, and interactive brainstorming sessions with participants. The results showed that the Social Media Literacy Strengthening Program to Avoid Hoaxes for Muslimat NU members in Demak Regency increased participants' awareness and skills, with pretest scores rising from 45% to 53% in posttest results. Thus, this program has provided participants with valuable knowledge to combat the spread of invalid information on social media. Abstrak Penggunaan internet di Indonesia, khususnya di kalangan perempuan, telah menunjukkan peningkatan signifikan dengan tingkat penetrasi mencapai 49,1% pada tahun 2024. Namun, peningkatan ini tidak sejalan dengan tingkat literasi digital, khususnya dalam memilah informasi yang akurat, yang masih rendah di kalangan ibu rumah tangga. Hal ini terbukti dari berbagai kasus penyebaran informasi hoaks yang melibatkan perempuan sebagai pelaku utama. Dalam rangka mengatasi masalah ini, pengabdian ini berfokus pada kelompok Muslimat NU Kecamatan Sayung, yang mayoritas anggotanya adalah perempuan berusia di atas 45 tahun dan aktif menggunakan media sosial serta aplikasi pesan seperti WhatsApp dan Facebook. Kelompok ini dipilih karena karakteristiknya yang mencerminkan digital immigrant, yang rentan terhadap penyebaran hoaks karena keterbatasan pemahaman terhadap teknologi informasi dan komunikasi (TIK), serta berada di daerah yang mengalami kesenjangan digital. Kegiatan ini dilakukan menggunakan pendekatan berkonsep Participatory Learning and Action (PLA) yang bertumpu pada ceramah, diskusi, curah pendapat secara interaktif dengan peserta. Hasil Pelaksanan menunjukkan bahwa Program Penguatan Literasi Media Sosial untuk Menghindari Hoaks bagi anggota Muslimat NU di Kabupaten Demak berhasil meningkatkan kesadaran dan kemampuan peserta dengan prosentase pretest 45% meningkat pada hasil posttest 53%. Sehingga kegiatan ini dapat memberikan pengetahuan bagi peserta dalam menghadapi penyebaran informasi yang tidak valid di media sosial